Surface‐Mediated Release of a Small‐Molecule Modulator of Bacterial Biofilm Formation: A Non‐Bactericidal Approach to Inhibiting Biofilm Formation in Pseudomonas aeruginosa. Issue 7 (20th January 2013) - Broderick, Adam H.; Breitbach, Anthony S.; Frei, Reto; Blackwell, Helen E.; Lynn, David M.
Abstract We report an approach to preventing bacterial biofilm formation that is based on the surface‐mediated release of 5, 6‐dimethyl‐2‐aminobenzimidazole (DMABI), a potent and non‐bactericidal small‐molecule inhibitor of bacterial biofilm growth. Our results demonstrate that DMABI can be encapsulated in thin films of a model biocompatible polymer [poly(lactide‐co‐glycolide), PLG] and be released in quantities that inhibit the formation of Pseudomonas aeruginosa biofilms by up to 75–90% on surfaces that otherwise support robust biofilm growth. This approach enables the release of this new anti‐biofilm agent for over one month, and it can be used to inhibit biofilm growth on both film‐coated surfaces and other adjacent surfaces (e.g., on other uncoated surfaces and at air/water interfaces). Our results demonstrate a non‐bactericidal approach to the prevention of biofilm growth and provide proof of concept using a clinically relevant human pathogen. In contrast to coatings designed to kill bacteria on contact, this approach should also permit the design of strategically placed depots that disseminate DMABI more broadly and exert inhibitory effects over larger areas. In a broader context, the non‐bactericidal nature of DMABI could also provide opportunities to address concerns related to evolved resistance that currently face approaches based on the release of traditional microbicidal agents (e.g., antibiotics). Finally, the results of initial in vitro mammalian cell culture studies indicate that DMABI is not toxic to cells at concentrations required for strong anti‐biofilm activity, suggesting that this new agent is well suited for further investigation in biomedical and personal care contexts.